Histiocytic sarcoma in dogs: epidemiology, anatomopathology, and immunohistochemistry - Flávia S. Da Luz; Renata D. Mazaro; Gabriela Hartmann; Tereza Cristina Da Silva; Bruno Cogliati; Lilian R. Marques de Sá; Glaucia D. Kommers; Alexandre A. Tonin; Rafael A. Fighera (Pesquisa Veterinária Brasileira, 2025)
ABSTRACT: Histiocytic sarcomas have been described in veterinary medicine since 1980, but studies on the subject are still scarce. Based on this, the objective of this article is to describe the epidemiological, anatomopathological and immunohistochemical aspects of histiocytic sarcoma in dogs submitted to necropsy in a diagnostic service covering the midwestern region of Rio Grande do Sul State, Brazil. From 2007 to 2021, 4,310 dogs were necropsied, of which 598 died or were euthanized due to some type of cancer. At least 18 cases of histiocytic sarcoma were diagnosed, i.e., 3% of cancer deaths and 0.4% of total deaths. The criterion used to establish the definitive diagnosis and inclusion in the study was an interaction between characteristic histopathology and positive immunostaining for CD204. Almost all (17/18, 94.4%) of these patients were of a defined breed and were large, with the vast majority (14/18, 77.8%) being Rottweiler. There was a predominance of disseminated histiocytic sarcoma (15/18, 83.3%) affecting several organs, while 10 (66.7%) affecting the lungs, liver, spleen and lymph nodes were affected concomitantly. Of the few cases (3/18, 16.7%) diagnosed as localized histiocytic sarcoma, where lungs were affected. Five different presentation patterns were observed macroscopically, not mutually exclusive: multinodular, massive, diffuse, peribronchiolar, and placoid. The most affected organs were the lungs (17/18, 94.4%), lymph nodes (15/18, 83.3%), liver (13/18, 72.2%), spleen (12/18, 66.7%), kidneys (6/15, 60%) and heart (6/15, 40%). Other less affected organs included adrenals (4/15, 26.7%), skeletal muscle (diaphragm) (4/15, 26.7%), bones (2/15, 13.3%), pancreas (2/15, 13.3%), pericardial sac (2/15, 13.3%), joint (1/15, 6.7%), omentum (1/15, 6.7%) and parietal pleura (1/15, 6.7%). Histologically, histiocytic sarcoma was characterized by a non-delimited, mantle-shaped proliferation with a scant stroma of round cells, many markedly anaplastic, often giving the tumor a rather pleomorphic appearance. A hallmark was the occurrence of a variable, but often high, number of mono, bi and multinucleated giant cells (30-100 µm in diameter), which always had large nuclei (karyomegaly) formed by loose chromatin and with nucleoli almost always multiple and conspicuous. Although there are peculiarities in the neoplastic involvement in each affected organ, in general, this proliferation tends to obscure the affected parenchyma and often invades and obliterates lymphatic and blood vessels. About 90% of neoplastic cells, including the most anaplastic and many of the multinucleated ones, immunostained strongly for CD204 and MHC-II but not for CD11d, confirming that they were histiocytes, other than splenic/bone marrow macrophages. It is hoped that this information will contribute to a better characterization of histiocytic sarcoma in the canine species and may help veterinary pathologists in their diagnostic routines.